Building Information - Representation and Management Principles and Foundations for the Digital Era - Koutamanis, Alexander (Open textbook library., 2022)
The book presents a coherent theory of building information, focusing on its representation and management in the digital era. It addresses issues such as the information explosion and the structure of analogue building representations to propose a parsimonious approach to the deployment and utilization of symbolic digital technologies like BIM. It also considers the matching representation of AECO processes in terms of tasks, so as to connect to information processing and support both information management and decision taking.